Ence Of ESBL Bacteria In Baby Box Handle At Dr. Soetomo Hospital - Manik Retno Wahyunitisari; Martono Tri Utomo; Nicholas Fernando Purnomo (JURNAL WIDYA MEDIKA, 2020)
Health Associated Infection (HAI) in neonates can increase neonatal infection risk, which is a fairly frequent cause of neonatal death. Microorganisms that are quite often found to contaminate include gram-negative bacteria such as Escherichia coli and Klebsiella pneumoniae. Gram-negative bacteria are also quite often found to have resistance to antibiotic therapy that is usually given, especially actlactam, and will increase the degree of disease to mortality, this bacterium is called ESBL. The study was conducted to determine the level of ESBL bacterial contamination in health facilities at Dr. Soetomo general hospital. Swabs are taken and biochemical tests were done to identify pathogen species. These isolates were also tested for ESBL production by the double-disc synergy test (DDST). There were 30 samples that contaminate the handle of the baby box, 2 of which (6.67%) tested positive for ESBL. With good hand hygiene, the use of disinfectants in medical devices, floors, walls, and doors, maintenance and replacement of tap water filters, and regular monitoring can reduce the number of bacterial contamination.